Dr Tom Shinder's configuring ISA Server 2004 - Shinder, Thomas W.; Shinder, Debra Littlejohn (Rockland, Mass. ; [Great Britain] : Syngress, 2005)
Dr. Tom and Debra Shinder have become synonymous with Microsoft's flagship firewall product ISA Server, as a result of Tom's prominent role as a member of the beta development team, and Tom and Deb's featured placement on both Microsoft's ISA Server Web site and ISAserver.org. Tom and Deb's book on the first release of the product "Configuring ISA Server 2000" dominated the ISA Server 2000 book market having sold over 40,000 copies worldwide, and the ISA Server community is eagerly awaiting Tom and Deb's book on ISA Server 2004, which is the dramatically upgraded new release from Microsoft. Dr. Tom and Debra Shinder have become synonymous with Microsoft's flagship firewall product ISA Server, as a result of Tom's prominent role as a member of the beta development team, and Tom and Deb's featured placement on both Microsoft's ISA Server Web site and ISAserver.org. Tom and Deb's book on the first release of the product "Configuring ISA Server 2000" dominated the ISA Server 2000 book market having sold over 40,000 copies worldwide, and the ISA Server community is eagerly awaiting Tom and Deb's book on ISA Server 2004, which is the dramatically upgraded new release from Microsoft. This book will be featured prominently on the ISAserver.org home page as well as referenced on Microsoft TechNet and ISA Server Web pages. Tom and Deb's unparalleled technical expertise combined with prime on-line marketing opportunities will make this the #1 book again in the ISA Server market. * This book will provide readers with unparalleled information on installing, confiuguring, and troubleshooting ISA Server 2004 by teaching readers to: * Deploy ISA Server 2004 in small businesses and large organizations. * Learn how to configure complex DMZ configurations using ISA Server 2004's new network awareness features and built-in multinetworking capabilities. * Learn how to take advantage of ISA Server 2004's new VPN capabilities!
Includes index.
Keywords: Microsoft ISA server; Client/server computing; Electronic books